Analisis Komunikasi Pengendalian Stress Dengan Pendekatan Psikologi Dan Religius - Asti, Asti; Hasyim, Baso; Masmuddin, Masmuddin (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2026)
Stress is a condition experienced by everyone, regardless of socioeconomic background, and can be managed through transcendental communication. Therefore, the purpose of this study is to determine how transcendental communication controls stress within a psychological and religious approach. Its use in the Islamic approach emphasizes faith and devotion to Allah SWT through dhikr, prayer, and Quran recitation. This type of communication is also found in psychological approaches, particularly transcendental meditation. Research shows that religious practices, such as dhikr, prayer, and reading holy books, can help improve psychological and spiritual well-being. Research also shows that the combination of transcendental communication within psychological and religious approaches can provide more effective results in stress management.